Education Feature:: Table Point, Western Newfoundland - An Example of Disfiguration of a Famous Outcrop - Stouge, Svend; Knight, Ian (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary Unknown collectors have vandalised theclassical locality at Table Point, westernNewfoundland. Many fossils have beenremoved with more or less success. Inattempts to collect fossils applying rocksaws and chisels, debris of fossils orpartly removed fossils were left at thelocality. Because most geological locali-ties are not protected by law in New-foundland, we hope that geologists willdevelop a sense of responsibility towardsnature and towards other scientists sothat classical sites like Table Point will berespected in the future.